The current-voltage and capacitance-voltage characteristics of molecularly modified ?-carotene/n-type Si junction structure with fluorescein sodium salt - Aydin, M. E.; Yakuphanoğlu, Fahrettin; Kilicoglu, T. (Elsevier Science Sa, 2007)
beta-Carotene-FSS organic semiconductor/n-type Si structure has been characterized by current-voltage and capacitance-voltage methods. A deviation in I-V characteristic of the diode is observed due to effect of series resistance and interfacial layer. Cheung's functions were used to calculate diode parameters. The ideality factor, series resistance and barrier height values of the diode are n = 1.77,R(s) = 10.32 (10.39) k Omega and 0.78 eV. The obtained ideality factor suggests that Au/beta-carotene-FSS/n-Si Schottky diode has a metal-SiO(2) oxide layer plus organic layer-semiconductor (MIOS) configuration. The capacitance-voltage characterizations of Au/beta-carotene-FSS/n-Si diode at different temperatures were performed. The capacitance of the diode changes with temperature. The barrier height and ideality factor obtained from C-V curves are 0.67 eV and 1.68. The interface density properties of the diode are analyzed and the shape of the density distribution of the interface states is in the range of E(c) -0.49 to -0.62 eV. It is evaluated that the FSS organic layer controls electrical charge transport properties of Au/beta-carotene/n-Si diode by excluding effects of the P-carotene and SiO(2) residual oxides on the hybrid diode. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: inorganic/organic device; organic semiconductor; ideality factor